Future Tasks of the International Calvin Research - Neuser, Wilhelm H. (Hervormde teologiese studies, 1998)
With the word international, we think specifically of the worldwide research on Calvin. The term international also points to the international Calvin Congresses, of which, until now, six have been held. At the Congresses we try to combine the international research as well as to give a fresh impetus for research. The lectures of all the previous Congresses have been printed, with exception of the last Congress in Edinburgh, 1994, which is now being printed. The results of these Congresses are therefore easy to obtain - everyone can read them.The task leads to a double question:Which topics of Calvin research have been analysed and discussed succesfully until now? Which topics should urgently be researched in future?The first answer includes both a review of the previous six Congresses as well as a glance at recent Calvin literature; the second answer will be developed in the overview which follows, titled The future tasks of Calvin research.